2013
DOI: 10.1093/mnras/stt201
|View full text |Cite
|
Sign up to set email alerts
|

Connecting magnetic towers with Faraday rotation gradients in active galactic nuclei jets

Abstract: The idea that systematic Faraday Rotation gradients across the parsec-scale jets of Active Galactic Nuclei (AGNs) can reveal the presence of helical magnetic (B) fields has been around since the early 1990s, although the first observation of this phenomenon was about ten years later. These gradients are taken to be due to the systematic variation of the line-of-sight B field across the jet. We present here the parsec-scale Faraday Rotation distributions for the BL Lac objects 0716+714 and 1749+701, based on po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(90 citation statements)
references
References 30 publications
9
81
0
Order By: Relevance
“…They also state "Attempting to detect RM gradients in jets less than two beams wide is discouraged as the probability to detect false positives exceeds 0.02 even when a 3σ limit is used." This statement is not quite in keeping with their own Figure 30, which, as quoted in [9] and [64], seems to indicate that for a 3σ limit, the false positive rate is only 0.01 even at one and a half jet beams. Hovatta (private communication) has confirmed that the figure is correct and that the "0.02" in the text was a typographical error, and also points out that a 1% false positive rate becomes more significant in the context of large surveys like MOJAVE where well over 100 sources were observed.…”
Section: Rotation Measure Gradientsmentioning
confidence: 73%
See 4 more Smart Citations
“…They also state "Attempting to detect RM gradients in jets less than two beams wide is discouraged as the probability to detect false positives exceeds 0.02 even when a 3σ limit is used." This statement is not quite in keeping with their own Figure 30, which, as quoted in [9] and [64], seems to indicate that for a 3σ limit, the false positive rate is only 0.01 even at one and a half jet beams. Hovatta (private communication) has confirmed that the figure is correct and that the "0.02" in the text was a typographical error, and also points out that a 1% false positive rate becomes more significant in the context of large surveys like MOJAVE where well over 100 sources were observed.…”
Section: Rotation Measure Gradientsmentioning
confidence: 73%
“…This point has now been extensively investigated with Monte-Carlo simulations by Hovatta et al [8], and also by Gabuzda and co-workers [63], [9], [64]. Hovatta et al emphasize that thermal noise can generate high RMs and spurious gradients if the jet is less than two beams wide in polarization.…”
Section: Rotation Measure Gradientsmentioning
confidence: 99%
See 3 more Smart Citations